US GROWING STRATEGIC INTERESTS IN INDIA AND ITS IMPLICATIONS FOR PAKISTAN’S SECURITY - Umar Hayat (Journal of Religion and Society, 2024)
The article discusses the implications of the US growing strategic Interest India and its implications for Pakistan’s security. It argues that growing the US Interests in India would have strategic, political and socio-economic implications for Pakistan. At strategic level, the US is on the way to India in terms geostrategic goals, which can pose serious implications for Pakistan in terms of ‘Balance of power’ between India and Pakistan in the region due to their traditional rivalry. At political level, due to traditional rivalry India always wanted to isolate Pakistan in international politics. This strategic shift can easily harm the political status of Pakistan in international arena, and compel Islamabad to drag its policy towards eastward. At socio-economic level, Pakistan is essential to the region’s economic integration. This strategic shift will depend Pakistan economy on China. The emerging strategic relationship between the US and the India has serious strategic implications both at the regional and global levels. India's strategic fostering poses a serious threat to Pakistan's security in the region. By awarding the STA-1 status to India, the US has undermined regional stability and the global non-proliferation regime. Keywords: Nuclear Suppliers Group, Belligerent, Supersonic Fighter, Deterrence, Disarmament